2006
DOI: 10.1097/00008483-200601000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Exercise Training in Patients With Chronic Atrial Fibrillation

Abstract: Exercise capacity, heart rate variability, and QOL improved after 2 months of exercise training in patients with chronic AF. Heart rates at rest and during exercise decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Although evidence is limited, small studies reported that AF patients participating in aerobic exercise and muscle strengthening reported greater vitality and physical functioning, improved emotional health, and less symptom severity 2730. Some patients with AF become reluctant to engage in exercise for fear of triggering an AF episode or because they perceive themselves as too exhausted to exercise 12.…”
Section: Education and Counseling Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence is limited, small studies reported that AF patients participating in aerobic exercise and muscle strengthening reported greater vitality and physical functioning, improved emotional health, and less symptom severity 2730. Some patients with AF become reluctant to engage in exercise for fear of triggering an AF episode or because they perceive themselves as too exhausted to exercise 12.…”
Section: Education and Counseling Componentsmentioning
confidence: 99%
“…Some patients with AF become reluctant to engage in exercise for fear of triggering an AF episode or because they perceive themselves as too exhausted to exercise 12. Patients should be informed that exercise is safe, beneficial, and may actually promote an electrophysiologic environment that reduces the potential for triggered electrical activity which can induce AF 27. Patients who are very deconditioned or afraid of beginning an exercise program may benefit by a referral to a cardiac rehabilitation program for exercise training instruction and a short-term program of supervised exercise.…”
Section: Education and Counseling Componentsmentioning
confidence: 99%
“…However, regular exercise training is an effective non-pharmacological therapy to improve autonomic dysfunction in the older adult population,2,6 even with the presence of cardiovascular diseases such as heart failure and atrial fibrillation 7,8. For instance, higher cardiac sympathetic activity is an important predictor of mortality in this population, and exercise training improves this parameter, thereby decreasing the risk of negative outcomes 9.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Valderrama et al [68] referred to other studies using Short Form-36 (SF-36) as a research outcome. In eight of these studies, we found argument for measuring QOL or health-related QOL, referring to SF-36 as the most valid and widely applied tool [27,35,46,53,54,61,75,76]. In six of the papers [4,28,33,36,46,57], QOL or health-related QOL was defined as a multidimensional concept with subjective elements which was hard to assess and use as outcome in clinical trials.…”
Section: The Text Close Analysis Levelmentioning
confidence: 99%
“…This may be exemplified by arguments stating that SF-36 is a valid and widely applied tool [27,35,46,53,61,[74][75][76]. This kind of argumentation [81][82].…”
Section: Sign Of An Implicit Societal Agreementmentioning
confidence: 99%